Measurement of high-Q2 charged-current e+p deep inelastic scattering cross sections at HERA - Breitweg, J; Chekanov, S; Derrick, M; Krakauer, D; Magill, S; Musgrave, B; Pellegrino, A; Repond, J; Stanek, R; Yoshida, R; Mattingly, M; Abbiendi, G; et al. (2000)
The e+p charged-current deep inelastic scattering cross sections, dσ/dQ2 for Q2 between 200 and 60000 GeV2, and dσ/dx and dσ/dy for Q2 > 200 GeV2, have been measured with the ZEUS detector at HERA. A data sample of 47.7 pb-1, collected at a center-of-mass energy of 300 GeV, has been used. The double-differential cross-section dσ/dQ2 falls by a factor of about 50000 as Q2 increases from 280 to 30000 GeV2. The double differential cross section d2σ/dxdQ2 has also been measured. A comparison between the data and Standard Model (SM) predictions shows that contributions from antiquarks (ū and c̄) and quarks (d and s) are both required by the data. The predictions of the SM give a good description of the full body of the data presented here. A comparison of the charged-current cross-section dσ/dQ2 with the recent ZEUS results for neutral-current scattering shows that the weak and electromagnetic forces have similar strengths for Q2 above M2W, M2Z. A fit to the data for dσ/dQ2 with the Fermi constant GF and MW as free parameters yields GF = (1.171±0.034 (stat.)+0.026-0.032 (syst.)+0.016-0.015 (PDF)) × 10-5 Gev-2 and MW = 80.8+4.9-4.5 (stat.)+5.0-4.3(syst.)+1.4-1.3 (PDF) GeV. Results For MW, where the propagator effect alone or the SM constraint between GF and MW have been considered, are also presented.